Visualising the relationships between synoptic circulation type and air quality in Sydney, a subtropical coastal‐basin environment. (20th May 2016) - Jiang, Ningbo; Scorgie, Yvonne; Hart, Melissa; Riley, Matthew L.; Crawford, Jagoda; Beggs, Paul J.; Edwards, Grant C.; Chang, Lisa; Salter, David; Virgilio, Giovanni Di
ABSTRACT: Ozone and particle pollution are of concern for the Sydney basin, in particular during warm months (November to March) when pollution levels can exceed national standards. Previous studies on the relationship between synoptic circulation and air quality focused on high pollution days or aggregated air quality conditions over the region as a whole. This study provides both temporal and spatial analyses of the synoptic processes affecting warm‐month ozone and particle pollution in Sydney. A warm‐month synoptic catalogue was developed by applying the self‐organising map method to the NCEP/NCAR geopotential height reanalysis for south‐east Australia. The catalogue was linked to mesoscale meteorological features such as drainage flows and sea breezes, and subsequently to the spatial variability in air quality across the Sydney basin. The typical synoptic types commonly associated with high or low ozone and PM10 levels, as well as variations in visibility, were identified. The results suggest that, due to Sydney's subtropical coastal‐basin environment, the interaction between meso‐ and synoptic‐scale features determine local air quality conditions in the region, rather than the synoptic conditions alone. Emissions from bushfires appear to have considerable impacts on the synoptic modulation to visibility and PM10 levels, with such impacts tending to be more at a local scale. In contrast, no comparable impacts were found for ozone pollution. For ozone and visibility, the probability for an exceedance day under some synoptic types varied considerably over time, implying that there might have been a shift in the role of synoptic modulation to local air quality associated with changes in air emissions profiles. This study provides a leap in our understanding of the relationship between synoptic circulation and air quality in a coastal‐basin environment. The results are useful for improving air quality forecasting in Sydney, with the methodology developed readily applicable to similar regions elsewhere.